KEEFEKTIFAN HOMEROOM UNTUK MENINGKATKAN KETERBUKAAN DIRI SISWA SMP - Sastama, Girinda Dara; Muslim, Mudaris; Djannah, Wardatul (Universitas Sebelas Maret, 2017)
The objective of this research is to examine the effectiveness of interpersonal communication training through homeroom technique in group guidance to improve the self-disclosure of the students in Grade VIII of State Junior High School. This research used the quasi experimental method with the non-equivalent control group design. It involved two groups, experimental group and control group. Each group consisted of 10 students. The data of research were collected through questionnaire and observation sheet. They were analyzed by using the Mann-Whitney U?s test. The result of the Mann-Whitney U?s test shows that the p value = 0.001. The result of the observation sheet shows that there was an increase in the students? self-disclosure. Thus, the interpersonal communication training through homeroom technique in group guidance is effective to improve the self-disclosure of the students in grade VIII of State Junior High School